Rare renal embolic manifestation of left atrial myxoma: A case report. (April 2023) - Han, Shiwei; Pradhan, Jigyasha; Girishkumar, Hanasoge
Abstract: Introduction and importance: A complete occlusion of the renal artery due to atrial myxoma is a rare occurrence. Case presentation: Here we present a case of a completely occluded left renal artery caused by atrial myxoma emboli that presented with a 14-hour history of sudden onset sharp left flank pain radiating to the left lower quadrant of the abdomen, nausea, with preserved kidney function. Revascularization is unlikely to benefit the patient because it has been more than 6 h since the onset of ischemia. Anticoagulation therapy was initiated, followed by myxoma resection. The patient was discharged with no evidence of nephropathy. Clinical discussion: Anticoagulation with or without thrombolysis is the standard treatment strategy for renal artery embolism. Given the delayed presentation of renal artery occlusion and the nature of the embolism, revisualization is not beneficial for this case. Conclusion: Emboli of atrial myxoma caused renal artery occlusion is rare. Thrombolysis or surgical revascularization can be used to restore perfusion for renal artery embolism. However, the likelihood of benefit from revascularization must be assessed. Highlights: A complete occlusion of the renal artery due to atrial myxoma is a rare occurrence. Acute occlusion frequently manifests as sudden flank pain or abdominal pain, mimicking common conditions like nephrolithiasis. For the treatment of renal artery embolism, the likelihood of benefit from revascularization must be assessed.